2020
DOI: 10.3390/ijms21186808
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature-Responsive Poplar lncRNAs Modulate Target Gene Expression via RNA Interference and Act as RNA Scaffolds to Enhance Heat Tolerance

Abstract: High-temperature stress is a threat to plant development and survival. Long noncoding RNAs (lncRNAs) participate in plant stress responses, but their functions in the complex stress response network remain unknown. Poplar contributes to terrestrial ecological stability. In this study, we identified 204 high-temperature-responsive lncRNAs in an abiotic stress-tolerant poplar (Populus simonii) species using strand-specific RNA sequencing (ssRNA-seq). Mimicking overexpressed and repressed candidate lncRNAs in pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…For instance, lncRNAs may be involved in ripening and softening in kiwifruit via regulating the expression of genes involved in starch and sucrose metabolism, brassinosteroid biosynthesis, and plant hormone signal transduction [48]. A recent study showed that lncRNAs regulate expression of target genes to enhance high-temperature tolerance in poplar [49]. LncRNAs are also found to play regulatory roles in the stress response in cucumber plants [50].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lncRNAs may be involved in ripening and softening in kiwifruit via regulating the expression of genes involved in starch and sucrose metabolism, brassinosteroid biosynthesis, and plant hormone signal transduction [48]. A recent study showed that lncRNAs regulate expression of target genes to enhance high-temperature tolerance in poplar [49]. LncRNAs are also found to play regulatory roles in the stress response in cucumber plants [50].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA cis-action is predicted by searching all coding genes within the 10-kb upstream and downstream of the target lncRNA, and these neighboring genes may be regulated by lncRNAs. The lncRNA trans-action was predicted based on nucleic acid base pairing [29]. The GO and KEGG enrichment analyses of the lncRNA target genes were conducted.…”
Section: Cisand Trans-target Gene Prediction Of Lncrnasmentioning
confidence: 99%
“…lncRNAs influence the formation of tension wood by regulating ARF s in Catalpa bungei ( Xiao et al, 2020 ). lncRNAs are widely involved in the secondary growth, GA response, heat tolerance, low nitrogen stress, salt stress, and other life processes of poplar ( Chen et al, 2016 ; Tian et al, 2016 ; Ci et al, 2019 ; Ma et al, 2019 ; Song et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%